Exploring Eggshell Waste and Calotropis gigantea Fibers for Eco-Friendly Ceiling Board Applications - Mahaputri, Ida Ayu; Adnyaswari , Made Diah Adi; Amanatullah, Muhammad Risqi; Tonyes, Silvia Gabrina; Ciawi, Yenni (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
The prohibition of asbestos in ceiling board production, due to its serious health risks, has prompted the search for safer and more sustainable alternatives. Current solutions often rely on non-renewable synthetic fibers, which pose environmental concerns. This study investigates the potential of using two abundant tropical waste materials—Calotropis gigantea leaves and eggshells—as renewable reinforcements in biocomposite ceiling boards. In Indonesia, eggshell waste from households and the food service industry amounts to approximately 483,920 tons annually, while C. gigantea grows widely along the country's coastal areas. The biocomposites were formulated by combining leaf fiber powder and eggshell-derived calcium carbonate (32.63–33.92% CaCO₃) in a resin matrix at various ratios. The resulting panels were evaluated through density, water absorption, drop resistance, and gradual heating tests. All samples exceeded the national density standard (SNI 03-2105) and demonstrated superior water and thermal resistance compared to commercial gypsum and kalsiboard panels. No sample failed under impact or heating up to 200°C. The presence of CaCO₃ contributed to improved mechanical and thermal performance while supporting the substitution of cement-based materials. These findings demonstrate the feasibility of utilizing post-consumer and plant-based tropical waste in environmentally friendly construction materials, offering a promising pathway for sustainable resource use, waste reduction, and green building practices in tropical regions.